Reflections on Radicalism in Social Work History: Moving Forward in a Difficult Time. Issue 3 (2nd September 2022) - Lundy, Colleen; Jennissen, Therese
ABSTRACT: This paper is a call for social workers to engage in discussions about the future of our profession. It draws on social work history and uses examples of the contributions of radical/socialist/Marxist social workers who faced challenging times and who promoted radical responses for creating a more just society. While the paper focuses on social work specifically, it was developed against a broader backdrop of cross-disciplinary literature of radicalism and critiques of the welfare state and social policy generally. The paper focuses mainly on Canada but because the histories are closely linked, there are also examples from the USA, and Great Britain. It includes a section on the role of social work education and the importance of using critical pedagogy in preparing social workers to advance social change, social justice, and human rights. And finally, some thoughts are provided on how social work might move forward.